Variety discrimination in pea (Pisum sativum L.) by molecular, biochemical and morphological markers - Smykal, Peter; Horacek, Jiri; Dostalova, Radmila; Hybl, Miroslav (Journal of applied genetics, 2008)
The distinctness, uniformity and stability (DUS) requirements involve expensive, space- and time-consuming measurements of morphological traits. Moreover, for a majority of traits, interactions between genotype and environment complicate the evaluation. Molecular markers have a potential to facilitate this procedure, increase the reliability of decisions, and substantially save the time and space needed for experiments. We chose 25 varieties of pea (Pisum sativum L.) from the list of recommended varieties for cultivation in the Czech Republic, and made both a standard classification by 12 morphological descriptors and a classification by biochemical-molecular markers. Two isozyme systems, 10 microsatellite loci, 2 retrotransposons for multilocus inter-retrotransposon amplified polymorphism (IRAP), and 12 retrotransposon-based insertion polymorphism (RBIP) DNA markers were analysed. The main objective of the study was to examine the potential of each method for discrimination between pea varieties. The results demonstrate a high potential and resolving power of DNA-based methods. Superior in terms of high information content and discrimination power were SSR markers, owing to high allelic variation, which was the only biochemical-molecular method allowing clear identification of all varieties. Retrotransposon markers in RBIP format proved to be the most robust and easy to score method, while multilocus IRAP produced informative fingerprint already in a single analysis. Isozyme analysis offered a fast and less expensive alternative. The results showed that molecular identification could be used to assess distinctness and complement morphological assessment, especially in cases where the time frame plays an important role. Currently developed pea marker systems might serve also for germplasm management and genetic diversity studies.
Keywords: Polymorphism, Genetic; DNA rostlinná; Microsatellite Repeats; Species Specificity; mikrosatelitní repetice; hrách setý; retroelementy; DNA, Plant; biologické markery; druhová specificita; Pisum sativum; Biomarkers; Retroelements; polymorfismus genetický